2015
DOI: 10.1021/sb500343g
|View full text |Cite
|
Sign up to set email alerts
|

A Competitive Flow Cytometry Screening System for Directed Evolution of Therapeutic Enzyme

Abstract: A ligand-mediated eGFP-expression system (LiMEx) was developed as a novel flow cytometry based screening platform that relies on a competitive conversion/binding of arginine between arginine deiminase and arginine repressor. Unlike product-driven detection systems, the competitive screening platform allows to evolve enzymes toward efficient operation at low substrate concentrations under physiological conditions. The principle of LiMEx was validated by evolving arginine deiminase (ADI, an anticancer therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…Absorbance was measured at 490 nm using an MTP reader (Tecan Sunrise; Tecan Group AG, Zürich, Switzerland). The ammonia‐detection system was used for detection of the kinetic data of non‐PEGylated and PEGylated PpADI variants as described in the previously published paper (Cheng, Kardashliev, et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbance was measured at 490 nm using an MTP reader (Tecan Sunrise; Tecan Group AG, Zürich, Switzerland). The ammonia‐detection system was used for detection of the kinetic data of non‐PEGylated and PEGylated PpADI variants as described in the previously published paper (Cheng, Kardashliev, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, a PpADI variant M31 was identified with significantly improved activity after several rounds of directed evolution campaigns with biosensor‐based high‐throughput screening (F. Cheng, Kardashliev, et al, ; F. Cheng, Tang, & Kardashliev, ). The in vitro tumor cell line tests showed that M31 displayed the dramatically reduced IC 50 values against melanoma cell lines SK‐MEL‐28 (0.02 µg/ml; 0.24% of WT) and G361 (0.02 µg/ml; 0.45% of WT).…”
Section: Introductionmentioning
confidence: 99%
“…Such concentrations are one order of magnitude higher than those of many metabolites in living cells or in blood plasma (e.g., in blood, [arginine] ≈100 μM) . A ligand‐mediated eGFP‐expression system (LiMEx) was developed by Cheng et al as a novel flow cytometry‐based screening platform that relies on a competitive conversion/binding of arginine between arginine deiminase and an arginine‐binding repressor protein . Unlike production‐driven detection systems (Figure A), the competitive screening platform allows to evolve enzymes toward more efficient operation at or below physiological substrate concentrations (Figure B).…”
Section: Tf‐based Screening Systems For Strain Evolutionmentioning
confidence: 99%
“…Other therapeutic enzymes could be conceptually evolved via LiMEx. For instance, asparaginase, a drug for treatment of leukemia, could be evolved by an “Asp‐LiMEx system” based on a competition between L ‐asparagine operon repressor (AnsR) and asparaginase toward asparagine (physiological concentration ≈0.1 mM) …”
Section: Tf‐based Screening Systems For Strain Evolutionmentioning
confidence: 99%
“…Nowadays, protein engineering by directed evolution has become a standard method to tailor enzyme properties in academia and industry (mainly for biocatalysis 8 purposes). Novel application fields in material science 9 and medical science [10][11][12] will likely lead to a further growth in directed evolution reports despite that the development time for improving enzymes by directed evolution are often still too long to be implemented as a standard operation in process development. Till today most directed evolution campaigns are performed in a traditional manner, in which usually random mutagenesis libraries are generated through epPCR with low mutations frequencies (1 to 3 mutations per 1000 bp) and screened (MTP format; often 1000-2000 variants) in order to obtained improved variants.…”
Section: Introductionmentioning
confidence: 99%